Fiscalização eletrônica: análise da eficácia na redução dos acidentes de trânsito - Uberlândia 2004 a 2006 - Sousa, Maria Cecília de (2008)
In Brazil, every year, about 350 thousand accidents happen with victim, from which more than 33 deaths result and around 400 thousand injured or invalids, victims from traffic accidents, turned into a deep economic and problem that also involves public health. In this context, it is observed an accelerated growth of purchasing of private vehicles, due to the necessity of moving quickly producing an undesired and unsustainable scenario when it refers to daily moving. This dispute for space and time inducts the conductor to get into traffic accidents or to commit infractions that many times are sued by the competent organ or by equipments of electronic inspection. There fore becoming the objective of this study to evaluate the importance of the installation and maintenance of electronic inspection, as a tool used in the reduction of traffic accidents and its gravity, in the area of influence of these equipments, in the period of 2004 to 2006. While analyzing the data bank of the accidents, it was observed a considerable change as to the growth of numbers of victims, evolving the lightly injured and the bad injured in the period from 2004 to 2005, however, the subsequent period presented a reduction to the number of bad injured and fatal victims. The main cause of traffic accidents in Uberlândia was the disregard to road signs regulation in crossings, having as possible causes the excess of speed and conductor s distraction. The hoist of the traffic accidents in the area of influence of radars occurred by analysis of data bank of these accidents, in the period proposed, observing an annual growth of 20% approximately comparing from the year of 2004 to 2005 and of 30% from2005 to 2006, however about severity, it is noticed a growth of approximately 7% from the year of 2004 to 2005, and in the period from 2005 to 2006, a fall occurred in the same proportion. As to the accidents occurred under the influence of electronic spines, in some cases, it was evidenced a growth of approximately 265% from 2004 to 2005, however the severity raised in an average of 5, 35%. While researching the type of infraction committed by conductors, with higher re-occurrence in the radars analyzed, it is noticed that in the year of 2005 there have been registered a superior number of infractions referent the traffic lights out breaking in relation to the year of 2006 and as integrating the informations of the data bank of the accidents e of the registered occurrences, it is noticed that offender conductors do not intimidate themselves with the penalties predicted in CTB (Brazilian Traffic Legislation), as analyzing the occurrences in 2006 it was observed that only 15 automobiles were taken for 230 times, all of them commiting infractions of grave or very grave nature, and a single vehicle got involved in AT for three times and ran away from the scene. The certainty of impunity motivates the conductor to commit infractions, putting other s life in danger, and making it impossible to reduce the traffic accidents and its gravity, and only the electronic supervising is not capable of reaching this objective. Therefore, it is observed that the information generated by electronic supervising and data bank of the ATs, needs to be defunded between the security organs and supervising, offering reliability in the execution of punishments to the conductors reducing the number of traffic accidents and its severity, besides making it impossible that vehicles go on without being legally licensed and with fake license plates and its conductors remain with excess of points on his/her license to drive, committing infractions and causing accidents with victims.